THE FLOODING FORECAST GIS-MODEL OF THE KHERSON REGION - AKSOM, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The article discusses problems of the GIS model technique creation for flooding forecast. The GIS integration data algorithm for spatial analysis is submitted.